Quality assurance for rotary screen printed wiring backplanes with automated roll-to-roll electrical test equipment. (9th April 2019) - Happonen, Tuomas; Kokko, Tuomas; Juntunen, Eveliina; Rönkä, Kari
Abstract: The roll-to-roll (R2R) printing process enables large-scale manufacturing of conductive wirings for the system integration of printed and hybrid electronics. As the number of R2R printed units in a run is typically high, a systematic approach is required to verify the outcome of manufacturing process extensively. This study presents a piece of automated R2R testing equipment, which is capable of the comprehensive electrical testing of printed and flexible electronics, and discusses the main findings provided by the test system in a use case of an R2R printed wiring backplane for a large-area display element. The automated R2R tester utilizes a bed-of-nails test method incorporated into the reeling equipment as a stop and go process. In this scheme, a bed-of-nails is a layout-specific test fixture providing physical contacts on the web. The actual measurement operations are performed by general-purpose electrical test equipment through standard industrial buses. Overall, the movement of the web containing printed electronics and the test operations for these are controlled by a test automation software. In this study, the R2R functional tester is utilized to evaluate the outcome of a rotary screen printing process for a large area backplane wiring of s 7 × 20 RGB LED matrix. The study presents the needed test cases for the full test coverage of printed wiring at an area of approximately 190 mm × 405 mm in each backplane unit. As the roll length is over 150 meters, the testing process systematically produces over 100 000 resistance measurement results to evaluate the manufacturing process yield and process variations from an electrical perspective. The paper concludes the main test results, and discusses the usability of the developed testing system and the protocol in this use case application.